2021
DOI: 10.3389/fmolb.2021.652443
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide-Resistant Progression of Castration-Resistant Prostate Cancer Is Driven via the JAK2/STAT1-Dependent Pathway

Abstract: Previous studies showed that CXCR7 expression was upregulated after enzalutamide (ENZ) treatment, and an increased level of CXCR7 could increase the invasion, migration, and angiogenesis of castration-resistant prostate cancer (CRPC) cells. This study demonstrated that the levels of p-JAK2, p-STAT1, C-Myc, and VEGFR2 were significantly reduced after CCX771, a specific CXCR7 inhibitor, treatment. This effect further increased after the combination treatment of ENZ and CCX771. Then, we verified that targeting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…On the other hand, inhibitors of WNT/ β -catenin (XAV-939), AKT (Capiversatib), HDAC (Panobinostat) and proteosome/NF κ B (Bortezomib) all demonstrated an inhibitory effect or trend on prostate regeneration (Figure 6J), implicating these pathways in driving L1 generation and L1 regenerative activities. We also find JAK/STAT, which has received a lot of attention recently in relation to advanced PCa lineage plasticity 7880 , to be one of the pathways deregulated in L1; however, we do not see any deregulation or enrichment of Stat motifs with castration in our scATAC studies. Furthermore, STAT chromatin recruitment has not been demonstrated in any of the recent studies, leaving us to wonder how JAK/STAT may be regulating treatment-induced plasticity.…”
Section: Discussioncontrasting
confidence: 62%
“…On the other hand, inhibitors of WNT/ β -catenin (XAV-939), AKT (Capiversatib), HDAC (Panobinostat) and proteosome/NF κ B (Bortezomib) all demonstrated an inhibitory effect or trend on prostate regeneration (Figure 6J), implicating these pathways in driving L1 generation and L1 regenerative activities. We also find JAK/STAT, which has received a lot of attention recently in relation to advanced PCa lineage plasticity 7880 , to be one of the pathways deregulated in L1; however, we do not see any deregulation or enrichment of Stat motifs with castration in our scATAC studies. Furthermore, STAT chromatin recruitment has not been demonstrated in any of the recent studies, leaving us to wonder how JAK/STAT may be regulating treatment-induced plasticity.…”
Section: Discussioncontrasting
confidence: 62%
“…Furthermore, to confirm the relationship between MnSOD and CXCR7/4, we overexpressed MnSOD in breast cancer cells. Interestingly, overexpression of MnSOD was observed to increase the level of CXCR7/4, and it was found that the protein expression level of the JAK/STAT pathway increased upon stimulation by CXCR7/4 [ 53 , 54 ]. In addition, overexpression of MnSOD induced invasion and migration of breast cancer cells, which was observed to be inhibited by LEE.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that MAPK inhibitors resensitize CXCR7 + CRPC to enzalutamide ( 20 ). Others have demonstrated that JAK2/STAT1 inhibition in combination with enzalutamide decreases the CXCR7-driven CRPC tumor growth ( 63 ). In the current work, we identify AURKA as a major mediator of CXCR7-driven PCa and show that AURKA inhibition reduces tumor growth.…”
Section: Discussionmentioning
confidence: 99%